Adolescents, Pornography Use, and Problematic Pornography Use: A Rapid Systematic Review of Longitudinal Studies - Mestre-Bach, Gemma; Potenza, Marc N. (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2025)
This rapid systematic review aimed to examine longitudinal studies that assessed pornography and problematic pornography use and their associations with specific features in adolescents. This review was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)guidelines. Longitudinal studies that examined pornography or problematic pornography use in adolescents were included. Forty-four longitudinal studies were included. The main themes explored were 1) sexual behaviors; 2) sexual risk behaviors; 3) sexual satisfaction; 4) permissiveness; 5) sexual aggression, dating victimization, and rape myths; 6) academic performance; 7) COVID-19 pandemic; 8) religiosity; 9) psychopathology, psychological well-being, and life satisfaction; and 10) other factors such as desensitization to sexual content, age of first exposure, types of pornography consumed, and individual and contextual variables. The findings were heterogeneous, with some studies indicating significant association between pornography use and these variables, whereas in other areas, the results were inconsistent. These findings highlight the need for further longitudinal research to clarify the relationship between types and patterns of pornography use in adolescents.